First-row transition metal complexes of a phosphine-silylene- based hybrid ligand - Akhtar, Ruksana; Kaulage, Sandeep H.; Sangole, Mayur P.; Tothadi, Srinu; Parvathy, Parameswaran; Parameswaran, Pattiyil; Singh, Kirandeep; Khan, Shabana (Inorganic Chemistry, 2022)
We have prepared two new silylene-phosphine-based hybrid ligands Si{N(R)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)} [R = TMS {trimethylsilyl} (1) and TBDMS {tert-butyldimethylsilyl} (2)], which possess two donor sites. Furthermore, the treatment of the bidentate ligand 1 with base metal halides {FeBr2, CoBr2, NiCl(2)middotdme [nickel chloride(II) ethylene glycol dimethyl ether]} and 2 with NiBr(2)middotdme [nickel bromide(II) ethylene glycol dimethyl ether] afforded four-coordinate six-membered metal complexes 3-6, respectively, which feature coordination from both Si(II) and P(III) sites. Subsequently, complexes 3 [(FeBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 4 [(CoBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 5 [(NiCl2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], and 6 [(NiBr2)Si{N((SiBuMe2)-Bu-t)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}] are studied for their redox and magnetic properties with the help of UV-vis spectroscopy, cyclic voltammetry, SQUID magnetometry, and theoretical calculations. Complexes 3-6 were found to display a paramagnetic behavior. All the compounds are well established by single-crystal X-ray diffraction studies.

Hybrid silylene-Pd catalyst: efficient C-N cross-coupling of sterically bulky amines and chiral amines - Kaulage, Sandeep H.; Parvin, Nasrina; Khopade, Kishor V.; Khan, Shabana (Chemical Communications, 2024)
Herein, we report a catalytic system with N-heterocyclic silylene (NHSi)-phosphine-based hybrid bidentate ligands [PhC(NtBu)2SiN(PR2)(2,6-iPr2-C6H3)] and Pd(dba)2, which serves as an effective catalyst for C-N cross-coupling of a wide range of sterically bulky amines and optically active amines, which is challenging otherwise. Herein, we report a hybrid silylene-based bidentate ligand (SiNP)-Pd(0) catalytic system, which performs the C-N coupling of difficult substrates, e.g., sterically bulky amines and chiral amines.

Rongalite-promoted self-dimerization of 3-acylidene-2-oxindoles: a diastereoselective route to synthesis of bispirooxindoles - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kaulage, Sandeep H.; Kinage, Anil K. (Organic & Biomolecular Chemistry, 2025)
A facile and efficient one-pot rongalite-mediated self-dimerization of 3-acylidene-2-oxindoles has been developed for the diastereoselective synthesis of highly functionalized dispirocyclopentanebisoxindoles. The reaction proceeds via a domino sequence involving intermolecular Michael addition followed by intramolecular aldol cyclization under basic conditions. Rongalite, an inexpensive and readily available reagent (similar to\$0.03 per g), plays a crucial role in promoting the transformation, offering significant advantages such as operational simplicity, step economy, scalability to gram-scale synthesis, and potential for post-functionalization. This methodology provides an efficient route to structurally complex oxindole frameworks with high stereocontrol, demonstrating broad synthetic utility.

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.

Steric-bulk directed polymerization of ethylene to disentangled ultra-high molecular weight polyethylene - V. Bodkhe, Dnyaneshwar; Patel, Ketan; Shaikh, Maulali H.; Kaulage, Sandeep H.; Mahajan, Digvijay; Pol, V. Harshawardhan; Chikkali, Samir H. (European Polymer Journal, 2026)
{The electron-withdrawing pentafluorophenyl phenoxy-imine-derived titanium complexes are known to produce ultrahigh molecular weight polyethylene (UHMWPE). However, cyclohexyl phenoxy-imine-derived zirconium complexes have been reported to produce low molecular weight polyethylene. The disparity between the two types of polyethylenes and the two types of catalysts can be bridged if a titanium complex bearing sterically bulky groups is made to produce UHMWPE. We report steric bulk-directed cyclohexyl phenoxy-imine titaniumcatalyzed synthesis of UHMWPE in a disentangled state. The influence of steric bulk in a phenoxy-imine-cyclohexyl ligand framework on titanium complex formation and subsequent ethylene polymerization was investigated through a combined computational and experimental approach. Density functional theory (DFT) and buried volume analyses indicated that increasing steric demand from -H to -Me to -tert-Bu substituents enhances the buried volume around the metal center, potentially favoring high molecular weight polyethylene formation. Guided by these insights, three ligands, L1-L3, were synthesized in excellent yields and fully characterized, including by single-crystal X-ray diffraction. Treatment of L1-L3 with a titanium precursor produced respective complexes, Cat.1-Cat.3, in good yields. These were characterized by NMR, IR, MS, and single-crystal X-ray diffraction. Upon activation with various co-catalysts [methyl aluminoxane (MMAO), triisobutylaluminum (TIBA), and tetrakis (pentafluoro phenyl) borate (BT)], these complexes initiated ethylene polymerizations. The catalytic activity increased from Cat.1 to Cat.2 with growing steric bulk, but decreased for the highly hindered Cat.3, likely due to restricted monomer access to the active site. Among the three, Cat.2, in combination with MMAO, showed the best performance under optimized conditions and produced ultrahigh molecular weight polyethylene (UHMWPE
Keywords: Metal catalysis; Phenoxy-imine ligand; Polyethylene; Titanium complexes; uHMWPE